Infection with human immunodeficiency virus (HIV) and cytomegalovirus in a London health district 1980-4. Issue 1 (February 1987) - Ross, M G; Burns, D M; Grundy, J E; Griffiths, P D
Abstract : By testing serum samples taken between 1980 and 1984 from men attending a department of sexually transmitted diseases, it was shown that antibodies to human immunodeficiency virus (HIV) first appeared in 1981. Homosexual men were significantly more likely to have antibodies to HIV and to cytomegalovirus (CMV) than were heterosexual men attending the same clinic. This shows that homosexuals are exposed to both HIV, the cause of the acquired immune deficiency syndrome (AIDS), and to CMV, which can reactivate to cause life threatening disease once immunosuppression has developed. All homosexuals, not just those with antibodies against HIV, had raised levels of CMV antibodies. This suggests that they experience frequent antigenic stimulation after reinfections with CMV or reactivation of endogenous virus.